Cultural perspectives of stunting prevention: A systematic review - Alfianti, Khalifatus Zuhriyah; Yunitasari, Esti; Armini, Ni Ketut Alit (Pediomaternal Nursing Journal, 2023)
Introduction: Developmental delays in children are signs of chronic malnutrition brought on by unfavorable circumstances since birth. Throughout the first 1000 days of life, stunting might increase mortality and disrupt bodily processes. Toddler malnutrition can also result from their culture, traditions, and social food. This study sought to synthesize earlier research that offered an overview of the cultural perspective on stunting prevention.Methods: Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) Guidelines were employed in the research design, and four databases were used for the literature search method (Scopus, PubMed, ProQuest, and Google Scholar) To find relevant articles, use the Boolean operator "stunting” OR "stunted” AND "culture” OR "cultural” AND "prevention” OR "prevent” by limiting 2017–2022 in English, full-text articles, and open access.Results: There are 12 papers addressing the cultural perspectives in the prevention of stunting, including parenting cultures on the role of fathers, parenting cultures on the role of grandmothers, and cultures of family empowerment. These studies are cross-sectional and quasi-experimental.Conclusions: Values emerge from interpersonal interaction and become part of the culture. A slightly different approach is required for communicating behavior change, especially in regions where ancestors' customs and beliefs are still practiced. Stunting can be avoided by using the cultural perspective as a preventative measure.Keywords: culture; health care; prevention; stunting